An empirical study on the issues and challenges faced by HR professionals in an IT company in Karnataka, India. (2016) - Saravanan, P.; Vasumathi, A.; Subashini, R.
Human resource management plays a vital role in a modern organisation because the management can obtain the organisational goals and objectives only with the cooperation and participation of the employees working within the organisation. HR acts as change agent and helps in driving the business decisions. The focus of HR moves towards the strategic HR functions such as talent branding, leadership development, performance management and engagement activities. The study addresses the issues and challenges faced by HR professionals on their day-to-day activities in the IT industry. The authors conducted a study for the sample size of 75 HR professionals from an Indian IT firm. The study found that the younger HR professionals are facing more stress when compared to aged HR professionals. The researchers found that years of experience is an important independent variable in predicting the level of stress faced by HR professionals than the other independent variables.